2008
DOI: 10.1007/s00431-008-0712-3
|View full text |Cite
|
Sign up to set email alerts
|

Clara cell secretory protein (CC16) as a peripheral blood biomarker of lung injury in ventilated preterm neonates

Abstract: The aim of this study was to assess the serum concentrations of Clara cell secretory protein (CC16) in association with acute and chronic lung injury in mechanically ventilated preterm neonates. Thirty-five preterm neonates (gestational age [GA] Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…Serum CC16 and IL-6 in preterm neonates K Sarafidis et al Disruption of the alveolar membrane with mechanical ventilation enhances leakage of CC16 from the alveoli into the bloodstream as documented in experimental models of acute lung injury, 21 adults ventilated for acute respiratory failure 9,11 and preterm neonates with RDS. 14 Nevertheless, although all types of mechanical ventilation cause structural disruption of the alveoli, 22 damage of the alveolar-capillary barrier and protein leakage was found to be less with HFOV, at least in animal studies. 23 This was not confirmed in this clinical study rejecting our initial hypothesis, because SIMV and HFOV were associated with comparable CC16 levels in the bloodstream.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Serum CC16 and IL-6 in preterm neonates K Sarafidis et al Disruption of the alveolar membrane with mechanical ventilation enhances leakage of CC16 from the alveoli into the bloodstream as documented in experimental models of acute lung injury, 21 adults ventilated for acute respiratory failure 9,11 and preterm neonates with RDS. 14 Nevertheless, although all types of mechanical ventilation cause structural disruption of the alveoli, 22 damage of the alveolar-capillary barrier and protein leakage was found to be less with HFOV, at least in animal studies. 23 This was not confirmed in this clinical study rejecting our initial hypothesis, because SIMV and HFOV were associated with comparable CC16 levels in the bloodstream.…”
Section: Discussionmentioning
confidence: 98%
“…14 Similarly, Loughran-Fowlds et al 13 reported increased serum CC16 in mechanically ventilated preterm neonates, speculating that high blood concentrations of the specific protein at birth may represent a protective mechanism during acute postnatal lung adaptation. CC16 is a protein with favorable action against hyperoxic injury, surfactant degradation and inflammation of the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC16 is a small protein secreted by epithelial Clara cells and an accepted biomarker of alveolar-capillary permeability 34 . Leakage of CC16 into the circulation is observed after lipopolysaccharide inhalation in healthy humans 71 , lung contusion 72 and mechanical ventilation in preterm neonates 36 or animal models 73 . Plasma CC16 concentrations are increased in ventilated ARDS patients 58 and predict poor outcomes such as greater mortality and fewer ventilator-free days 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration of neutrophil elastase (NE) is an indicator of alveolar recruitment 32 and activation of neutrophils during the development of lung injury 33 . Finally, plasma Clara cell protein 16 (CC16), an antiinflammatory protein secreted by the Clara cells of the distal respiratory epithelium, is a marker of acute epithelial lung injury 34,35 and increases in ventilated preterm neonates 36 and after 5-h ventilation during abdominal surgery in adults 37 .…”
Section: Introductionmentioning
confidence: 99%